2014
DOI: 10.1017/s0950268814003331
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Leptospira antibodies in wild boars (Sus scrofa) from Northern Portugal: risk factor analysis

Abstract: Leptospirosis is a zoonosis of worldwide distribution, caused by infection with pathogenic spirochaetes of the genus Leptospira. The wild boar (Sus scrofa), an important hunting species in Europe, seems to play a significant role in the epidemiological cycle of leptospirosis. A total of 101 serum samples from wild boar hunted in Northern Portugal were analysed for leptospiral antibodies detection by microscopic agglutination test. Sera were collected during hunting seasons (2011-2013) and tested with 17 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…(Chiari, Zanoni, Tagliabue, Lavazza, & Alborali, ), Leptospira sp. (Vale‐Goncalves et al., ), Mycobacterium bovis (Naranjo, Gortazar, Vicente, & de la Fuente, ) or the hepatitis E virus (Jori et al., ). In fact, a recent study in Corsica provided molecular evidence of transmission of hepatitis E virus strains between wild boar and domestic pig populations (Jori et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…(Chiari, Zanoni, Tagliabue, Lavazza, & Alborali, ), Leptospira sp. (Vale‐Goncalves et al., ), Mycobacterium bovis (Naranjo, Gortazar, Vicente, & de la Fuente, ) or the hepatitis E virus (Jori et al., ). In fact, a recent study in Corsica provided molecular evidence of transmission of hepatitis E virus strains between wild boar and domestic pig populations (Jori et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Leptospira DNA was found in kidneys of boars in Japan [ 21 ]. In addition, anti- Leptospira antibodies were found in 65.4% of wild boars in Portugal [ 22 ], and in 33% of feral hogs ( Sus scrofa ) in Florida, USA [ 23 ]. Results of the epidemiological link between consumption of boar meat and Leptospira exposure found in this study warrant for further research.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that pigs are the main host for serovar Bratislava, Muenchen, Pomona and Tarassovi [51][52][53]. Bratislava and Tarassovi in particular have been commonly detected in wild boars [54,55]. It has been suggested that wild boars may play a role in transmission to domesticated pigs.…”
Section: Discussionmentioning
confidence: 99%